Armenian Apocrypha relating to angels and biblical heroes - Stone, Michael E. (Early Judaism and its literature, 2016)
Cover; Table of Contents; Preface and Acknowledgments; Signs; Abbreviations; Manuscripts Published in This Book; Part One: Biblical and Associated Traditions; Part Two: Chronological Texts; Part Three: Angelological Texts; Part Four: Biblical Stories; Bibliography; Subject Index; Index of Persons and Places; Ancient Sources Index